Synthesis, Spectroscopic, Thermal and in vitro Antimicrobial Activity of Fe(III) and Mn(III) Metal Complexes of Semicarbazone - Somaiya, Chintan P.; Patel, Dinesh S.; Jani, Darshan H. (Asian Journal of Chemistry, 2020)
In this work novel pyrazolone based semicarbazone derivatives and their spectroscopic and biological activities were investigated. Pyrazolone based semicarbazone ligands and their Fe(III) and Mn(III) heterochelates were synthesized. The structure of semicarbazone ligands were confirmed by 1H NMR, IR, elemental analysis and their heterochelates were confirmed by thermal studies (TGA/DTG & DSC) and FAB mass spectroscopy. All the ligands and heterochelates were screened for antimicrobial study against Gram positive (Bacillus megaterium, Bacillus subtilis) and Gram negative (E. coli, Klebsiella) microorganisms. The results confirmed that semicarbazone based heterochelates have a great potential and significant for further investigation.